Antimicrobial Activity and Filtration Effectiveness of Nonwovens with Sanitized for Respiratory Protective Equipment - Gutarowska, Beata; Skóra, Justyna; Nowak, Ewelina; Łysiak, Izabela; Wdówka, Malwina (Institute of Biopolymers and Chemical Fibres, 2014)
The objective of the study was to optimise the production of bioactive filtration nonwovens with Sanitized® T 99-19, containing quaternary ammonium salts, by evaluating different production technologies (melt-blowing, needle punching), methods of biocide incorporation (bath, spraying), biocide concentration, and conditioning. The antimicrobial activity of nonwovens was tested against different microorganisms, from culture collection and workplaces, using the method AATCC 100. It was shown that the biological efficiency of nonwovens rose when the concentration of Sanitized was increased from 0.7% to 2%. Furthermore, higher biological activity was found in nonwovens subjected to a bath than in those which underwent spraying. The conditioning process did not significanty affect the antimicrobial activity of the nonwovens tested. As compared to melt-blown nonwovens, the needled variety were more efficient against both collection strains and those isolated from workplaces. Thus both types of nonwovens may be used for the production of bioactive halfmasks protecting the respiratory tract of workers exposed to microorganisms
Keywords: bioactive half-mask; antimicrobial nonwovens; Sanitized T9919; microorganisms